Human CD8+ T Cells Release Extracellular Traps Co-Localized With Cytotoxic Vesicles That Are Associated With Lesion Progression and Severity in Human Leishmaniasis - Koh, Carolina Cattoni; Wardini, Amanda B.; Vieira, Millene; Passos, Livia S. A.; Martinelli, Patrícia Massara; Neves, Eula Graciele A.; Antonelli, Lis Riberido do Vale; Barbosa, Daniela Faria; Velikkakam, Teresiama; Gutseit, Eduardo; Menezes, Gustavo B.; Giunchetti, Rodolfo Cordeiro; et al. (Frontiers in Immunology, 2020)
Cell death plays a fundamental role in mounting protective and pathogenic immunity. Etosis is a cell death mechanism defined by the release of extracellular traps (ETs), which can foster inflammation and exert microbicidal activity. While etosis is often associated with innate cells, recent studies showed that B cells and CD4+ T cells can release ETs. Here we investigate whether CD8+ T cells can also release ETs, which might be related to cytotoxicity and tissue pathology. To these ends, we first employed an in vitro system stimulating human CD8+ T cells isolated from healthy volunteers with anti-CD3/anti-CD28. Using time-frame video, confocal and electron microscopy, we demonstrate that human CD8+ T cells release ETs upon stimulation (herein LETs – lymphocyte extracellular traps), which display unique morphology and functional characteristics. CD8+ T cell-derived LETs form long strands that co-localize with CD107a, a marker of vesicles containing cytotoxic granules. In addition, these structures connect the LET-releasing cell to other neighboring cells, often resulting in cell death. After demonstrating the release of LETs by human CD8+ T cells in vitro, we went on to study the occurrence of CD8-derived LETs in a human disease setting. Thus, we evaluated the occurrence of CD8-derived LETs in lesions from patients with human tegumentary leishmaniasis, where CD8+ T cells play a key role in mediating pathology. In addition, we evaluated the association of these structures with the intensity of the inflammatory infiltrate in early and late cutaneous, as well as in mucosal leishmaniasis lesions. We demonstrated that progression and severity of debilitating and mutilating forms of human tegumentary leishmaniasis are associated with the frequency of CD8+ T cells n etosis, as well as the occurrence of CD8-derived LETs carrying CD107a+ vesicles in the lesions. We propose that CD8+ T cell derived LETs may serve as a tool for delivering cytotoxic vesicles to distant target cells, providing insights into mechanisms of CD8+ T cell mediated pathology.